NEEDED APPLICATION DESIGN FOR UNIFORMITY OF BIRTH PLACE INFORMATION ON THE NATIONAL IDENTITY CARD (KTP) - maisondra maisondra (Institut Pemerintahan Dalam Negeri, 2024)
Research for finding out about the non-uniformity in the writing of birthplace information in population and civil registration documents, especially identity cards (KTP), which include: differences based on classification or area level, to find out the causes and find solutions. The method used is a descriptive qualitative approach which aims to describe the current reality. Describe, record, analyze and interpret these conditions, namely regarding the writing of Place of Birth Information in population data and Civil Registration, especially KTP. The facts of this study show that: 1) There is regional level inconsistency in writing information on place of birth on population documents, especially KTPs, which consist of: some write the name of the province, write down the name of the district/city, write down the name of the sub-district, write down the name of the kelurahan/village, and so on, 2) There are no regulations that require writing down the description of Lahi's place, with the same area level. Usually, if the data on the KTP is not uniform, then the data on other population documents will also be different because the data on other population documents originates from the KTP. As a solution to this non-uniformity, you can provide an application design that only provides options for the name of the city/district in the Statement of Place of Birth.